A Study of Supply Chain Management for Preliminary Destination Brand Experience in North Sumatera, Indonesia - Miska Irani Tarigan; Arlina Nurbaity Lubis; Endang Sulistya Rini; Beby Karina F. Sembiring (International Journal of Supply Chain Management, 2020)
The development of tourism places is getting more attention in current era especially Lake Toba, North Sumatera, Indonesia. It aims to attracts many tourists. As one way to differentiate the identity of a product or service is by the brand. The brand experience emerges as an essential and effective in management and marketing. Thus, this study consider the brand experience as a factor in market competition. In conjuction with the issue, this study aims to identify the supply chain management for preliminary destination brand experience In North Sumatera, Indonesia. This quantitative study designed using the library, literature reviews and others relevance source. The data analyzed using the Matrix Strategic Position and Action Evaluation (SPACE). The results of the analysis found that the environmental stability of Lake Toba as tourism area categorized as medium position. Also, using the inelastic dimension of environmental stability (pricing), we found that the Lake Toba is still a tourist choice. In addition, the experience as the value of excellence to increase the tourist satisfaction.